Medicinsko nepojasnjena stanja - Ivetić, Vojislav (Medicinski razgledi, 2005)
Almost 20% of patients who consult their family physicians, present with physically unexplained symptoms. Diagnostic clues include multiple unexplainedsymptoms, usually in different organic systems, unclear symptoms, high health care utilization patterns and normal results from physical examination and diagnostic tests. Articles were found through a MEDLINE search. The search was performed utilizing the MeSH terms "medically unexplained symptom", "somatization", "somatoform disorders", "family medicine". Only papers in English were selected. Patients with medicaly unexplained symptoms are found in the following groups of patients: problematic patients, frequent visitors of family physicians office, patients with functional problems, anxious and/or depressive patients, patients with somatisation and somatoform disorders. Common symptoms that induce suspicion of medicaly unexplained symptoms are: fatigue, dizzines, headache, dispnea, syncopa, vomiting, dispepsy, insomnia, chest pain, aritmy, gastrointestinal problems (opstipation, diarrea), chronic pain... Family physicians are often feeling frustrated and responsable for patients discontent with their threatment in cases of medicaly unexplained symptoms. It is generaly believed that family physicians are not sufficiantly theoreticaly and practically educated to threat patients with medicaly unexplained symptoms. The process oftreating these patients is challenging, complex and poorly understood. In spite various strategies to treat such patients have been tried, effective management guidelines are still lacking. Difficulties in treating these patients represent a challenge for searching and developing new methods that would reduce expenses of diagnosis and treatment and lower the frequency of these patients visits to the family physician and their unnecessary direction to the specialists.
Keywords: Družinska medicina; Physician-Patient Relations; Family Practice; Somatoformne motnje; Zdravnik-bolnik, odnosi; Somatoform Disorders; zdravje; medicinsko nepojasnjena stanja